2015
DOI: 10.1071/am14030
|View full text |Cite
|
Sign up to set email alerts
|

Divergent foraging behaviour of a desert rodent, Notomys fuscus, in covered and open microhabitats revealed using giving up densities and video analysis

Abstract: We used a combination of giving up densities (GUD) and behavioural analysis from video footage to test the response of an Australian desert rodent, Notomys fuscus, to the experimental provision of cover microhabitat in the Strzelecki Desert, Australia. In many ecosystems, cover microhabitats are considered to be safe foraging locations for rodents. The response of bipedal desert rodents to cover microhabitats is less certain, with varied findings, due to their use of open habitats for fast travel. Notomys fusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This finding suggests that foxes at risk of a potentially fatal encounter with a dingo will try to get in and get out of an area as quickly as possible, spending as little time as possible on surplus behaviour and making the most of their opportunity to obtain resources. Similar 'get in-get out' behaviour has been observed in rodents that were presented with resource patches in areas of high and low predation risk (Morris et al 2015).…”
Section: Discussionmentioning
confidence: 55%
“…This finding suggests that foxes at risk of a potentially fatal encounter with a dingo will try to get in and get out of an area as quickly as possible, spending as little time as possible on surplus behaviour and making the most of their opportunity to obtain resources. Similar 'get in-get out' behaviour has been observed in rodents that were presented with resource patches in areas of high and low predation risk (Morris et al 2015).…”
Section: Discussionmentioning
confidence: 55%
“…This preference is likely due to their increased agility and capacity to avoid predators compared with their quadrupedal counterparts which select more sheltered microhabitats , with bipedal N. alexis selecting more open habitats than the quadrupedal P. hermannsburgensis and using escape rather than avoidance behaviour to reduce predation risk (Spencer et al 2014). Conversely, Morris et al (2015) found the dusky hopping-mouse (Notomys fuscus) to forage preferentially under cover. It was not clear whether other rodents occurred in this last study, but it is possible that hopping-mice may extend their activity to incorporate sheltered habitats if other rodent species are absent.…”
Section: Discussionmentioning
confidence: 84%